IMPLEMENTASI PELAYANAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN LAMPUNG SELATAN OLEH TIM KECAMATAN TANJUNG BINTANG - Pratama, Andika; Rosidah, Rosidah; Mosshananza, Hinfa (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
The problem in this study is that people in Tanjung Bintang District take approximately 2 hours to take care of population documents such as ID cards, family cards, birth certificates, and others. The mileage experienced by the community when handling documents is very difficult, time-consuming, and inefficient. This is a problem for today's society. The research method used is qualitative descriptive research, which is an analysis based on data obtained through interviews with informants, observation, and documentation. The results of the study, namely the Quality of Service of the Population and Civil Registration Office of South Lampung Regency by the Tanjung Bintang District Team, measured by five dimensions from Zeithhanl, Parasurama, and Berry, namely physical evidence (tangible), reliability (reliability), responsibility, assurance, and empathy (emphaty), are good enough, but there are still shortcomings. The existence of the Tanjung Bintang District Team is very helpful for the village community in terms of taking care of population documents that no longer need to go far to Disdukcapil Kalianda, so that it is more effective and efficient. In addition, findings regarding inhibiting factors in service by the Tanjung Bintang District Team are: limited space, officers who have never been given training in public services, lack of human resources, tools that depend on each other, and internet network disruption. Keywords: Implementation; Quality; Public Service